Peran Pengguna Media Sosial X dalam Pencegahan Bullying: Studi pada Remaja GBI Kamboja Depok - Hutasoit, Yosafat Sahala Tua (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bullying has become a phenomenon that has garnered global attention due to its negative impact on individual well-being. Particularly, the development of technology and the penetration of social media have expanded the scope of bullying, including at Gereja Bethel Indonesia (GBI) in Cambodia. This research aims to understand the role of teenagers in preventing bullying on social media, focusing on their contributions in finding solutions quietly. The study uses a qualitative approach with in-depth interviews with several active teenagers on social media platform X from the GBI Cambodia community. The research employs the concept of the Spiral of Silence. The findings indicate that GBI Cambodia teenagers play a crucial role in identifying, understanding, and responding to bullying on social media platforms. The study shows that church teenagers initially tend to feel afraid or hesitant to express opinions on bullying prevention due to their perception as a minority group. However, through interactions on social media platform X, some members of this minority group have managed to break the spiral of silence by courageously voicing their opinions. The results of this research provide valuable insights into the role of teenagers in combating bullying on social media. Practical implications include the need for a collaborative approach between teenagers, families, churches, and other relevant parties to develop effective solutions. Additionally, this study contributes theoretically to the understanding of how teenagers can become agents of change in fighting bullying in a digital context.